Abraham Lincoln and Robert Burns : connected lives and legends - Szasz, Ferenc Morton, 1940-2010 (Southern Illinois University Press, 2008)
Today the images of Robert Burns and Abraham Lincoln are recognized worldwide, yet few are aware of the connection between the two. In Abraham Lincoln and Robert Burns: Connected Lives and Legends, author Ferenc Morton Szasz reveals how famed Scots poet Robert Burns-and Scotland in general-influenced the life and thought of one of the most beloved and important U.S. presidents and how the legends of the two men became intertwined after their deaths. This is the first extensive work to link the influence, philosophy, and artistry of these two larger-than-life figures.>